2013
DOI: 10.1186/1471-2458-13-1081
|View full text |Cite
|
Sign up to set email alerts
|

Designing a theory- and evidence-based tailored eHealth rehabilitation aftercare program in Germany and the Netherlands: study protocol

Abstract: BackgroundCardiac rehabilitation programs aim to improve health status and to decrease the risk of further cardiac events. Persons undergoing rehabilitation often have difficulties transferring the learned health behaviors into their daily routine after returning home and maybe to work. This includes physical activity as well as fruit and vegetable consumption. Computer-based tailored interventions have been shown to be effective in increasing physical activity as well as fruit and vegetable consumption. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…The tunnelling feature was identified in many of the reviewed articles which described systems that provided tailored information based on the results of an assessment conducted on an individual user (46). This feature is presented in the systems in a variety of forms such as users sending weekly self-monitoring data via their mobile phone (48) which will become the basis for the tailored messages that they receive about their lifestyle management.…”
Section: Primary Task Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The tunnelling feature was identified in many of the reviewed articles which described systems that provided tailored information based on the results of an assessment conducted on an individual user (46). This feature is presented in the systems in a variety of forms such as users sending weekly self-monitoring data via their mobile phone (48) which will become the basis for the tailored messages that they receive about their lifestyle management.…”
Section: Primary Task Supportmentioning
confidence: 99%
“…Despite the culling process, some of the reviewed articles -which had indicated that an intervention had been conducted -were found to be discussions about a system that was still in the proposed stage of intervention (40) or the design and implementation stage (88) or the study details were presented but not the outcome (46,65). Tailoring also often appeared in conjunction with the dialogue support features as it can enhance the personalised experience of users.…”
Section: No Significant Differencesmentioning
confidence: 99%
“…The cross-sectional baseline data for the present analyses from the German study arm were analysed, due to significant differences between German and Dutch study participants (Storm et al, 2016). The complete study design was published in a study protocol (Reinwand et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…HAPA based social-cognitive variables, physical activity behaviour and physical activity habit was measured online via self-report questionnaires (Reinwand et al, 2013). All scales were validated and tested for reliability in a previous study (Lippke, Wienert, Kuhlmann, Fink, & Hambrecht, 2015;Wienert, Kuhlmann, Fink, Hambrecht, & Lippke, 2016;Wienert et al, 2017a;Wienert, Kuhlmann, Fink, Hambrecht, & Lippke, 2017b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation